Electroacupuncture Mechanisms in Managing Preoperative Anxiety and Postoperative Pain Chronification: A Review - Erasmus S; Lyu Z; Zhou J; Fang J; Liang Y (Journal of Pain Research)
Shannah Erasmus,1,* Zhengyi Lyu,2,* Jie Zhou,3 Jianqiao Fang,3 Yi Liang3 1International Education College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 2The Third Medical College, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Acupuncture, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Liang, Department of Acupuncture, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China, Email liangyiwww@126.comIntroduction: Postoperative hyperalgesic priming, exacerbated by preoperative anxiety, complicates pain management and recovery. Electroacupuncture (EA), a technique that combines traditional acupuncture with electrical stimulation applied through needles to enhance therapeutic effect, offers a potential solution by targeting multiple neurobiological pathways.Objective: This review investigates how EA addresses preoperative anxiety-induced postoperative hyperalgesic priming ie pain chronification, focusing on its mechanisms in three areas: preoperative anxiety, postoperative hyperalgesic priming, and the interaction between EA and these processes.Methods: A literature search across PubMed, ScienceDirect, and Google Scholar identified relevant studies on EA’s effects on neurobiological pathways related to anxiety and pain. The review synthesized findings to understand EA’s role in these contexts.Results: EA alleviates preoperative anxiety by influencing the body’s neurochemical and neurophysiological responses. It reduces inflammation, regulates stress hormones, and improves autonomic function. For postoperative pain chronification, EA modulates pain pathways, reduces inflammation, and affects receptor signaling, gene expression, and neurotransmitter systems.Conclusion: EA offers a promising approach to managing preoperative anxiety and postoperative pain. By addressing both the physiological and neurochemical pathways that contribute to pain and anxiety, EA has the potential to significantly improve clinical outcomes for patients undergoing surgery. Further research is needed to fully understand its mechanisms and optimize its application in clinical settings.Keywords: preoperative anxiety, chronic postoperative pain, hyperalgesic priming, electroacupuncture mechanisms, analgesic, anxiolytic